2014
DOI: 10.1152/jn.00297.2014
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting saturated LTP by broadly spaced episodes of theta-burst stimulation in hippocampal area CA1 of adult rats and mice

Abstract: Cao G, Harris KM. Augmenting saturated LTP by broadly spaced episodes of theta-burst stimulation in hippocampal area CA1 of adult rats and mice. J Neurophysiol 112: 1916 -1924. First published July 23, 2014 doi:10.1152/jn.00297.2014.-Hippocampal long-term potentiation (LTP) is a model system for studying cellular mechanisms of learning and memory. Recent interest in mechanisms underlying the advantage of spaced over massed learning has prompted investigation into the effects of distributed episodes of LTP ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 59 publications
2
46
0
2
Order By: Relevance
“…At P15, the next bout could stabilize the new connectivity, while in adults the next bout could recruit vesicles to new docking sites at the enlarged nascent zones. This interpretation is consistent with recent findings showing that sufficient time must pass before the initial LTP became unsaturated and a second bout of TBS could augment the potentiation (Babayan et al, 2012; Bell et al, 2014; Cao and Harris, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…At P15, the next bout could stabilize the new connectivity, while in adults the next bout could recruit vesicles to new docking sites at the enlarged nascent zones. This interpretation is consistent with recent findings showing that sufficient time must pass before the initial LTP became unsaturated and a second bout of TBS could augment the potentiation (Babayan et al, 2012; Bell et al, 2014; Cao and Harris, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…The studies also demonstrate that the facilitating effects of spacing, for both genotypes, align with the periodicity of afferent stimulation required to enhance hippocampal LTP (10,17). This results in a narrow time window for augmenting learning: Spaced trials were effective with a minimum of three trials spaced by 60 min while 20-or 120-min intervals did not improve retention scores.…”
Section: Discussionmentioning
confidence: 68%
“…We gave additional mice 5-min training daily for 6 d: OLM was still absent in the KOs indicating that they do not form a partial memory trace after 5 min of training. We focused on OLM because its retrieval depends on hippocampal field CA1 (11,14), which exhibits an elevated LTP threshold in Fmr1 KOs (7,8) and enhanced potentiation with spaced stimulation in WTs (10,17). However, Fmr1 KOs have more robust LTP impairments in other regions including cortex (6,(18)(19)(20)(21).…”
Section: Significancementioning
confidence: 99%
“…The required refractory period of ~1 hour between successive theta-burst stimuli to induce progressive increments in hippocampal LTP 46,47 may be in line with the first of these variants, which is that short intervals are insufficient for consolidation and consequent summation of memory traces. The refractory period appears to be necessary to complete the priming of dendritic spines that were stimulated, but not potentiated, by the first theta-burst stimulus.…”
Section: Recent Data and Learning Theoriesmentioning
confidence: 77%
“…Thus, studying the differential dynamics of dendritic spine remodelling following massed versus spaced stimuli is likely to provide insight into processes underlying the effectiveness of spaced training. Studies using rat hippocampal slices found that LTP induced by multiple trains of theta-burst stimuli was accompanied by extensive remodelling of synaptic ultrastructures 44,45 and that subsequent spaced trains of theta-burst stimuli, with intervals of 60 minutes or more between the trains, were needed for optimal reinforcement of LTP 46 . Stimulated dendritic spines were remodelled over a period of more than 1 hour, leading to enlargement of the existing functional postsynaptic density 45 and the presynaptic active zone 44 .…”
Section: Molecular Traces Of Timementioning
confidence: 99%